Pelatihan Kompetitif Bisnis Melalui Digitalisasi UMKM Kelurahan Banjarsari - Saputra, Muhammad; Nouvan, M. Ahadi; Triloka, Joko; Sari, Novita (Jurnal Publika Pengabdian Masyarakat, 2024)
Today's increasingly fierce business competition encourages Micro, Small and Medium Enterprises (MSMEs) to have a competitive advantage and a positive impact on business development or business. Banjarsari Village is a village in Metro City that has several Micro, Small and Medium Enterprises (MSMEs) with the findings that the use of technology or digitalization in running business operations has not been maximized, which is the urgency of implementing this community service activity. The community service activities were carried out at Banjarsari Village Hall within a period of 3 days with activities including website and social media training, product brand training, digital financial recording training, e-commerce training and business whatsapp. In the implementation of this service activity, it is focused on Micro, Small and Medium Enterprises (MSMEs), namely Yumna MSMEs engaged in the food business and batik canting as pilot MSMEs in this service activity. The output of this activity is where MSME players who are the pilot, namely Yumna MSMEs, are in the form of websites and social media, brands or brands, digital financial applications, e-commerce and business whatsapp